DANDELION KOK-SAGHYZ (TARAXACUM KOK-SAGHYZ L. RODIN) AS A ONE-YEAR CULTURE DEVELOPED UNDER CONDITIONS OF SOUTHEAST KAZAKHSTAN - Uteulin Kairat; Bari Gabit; Zheksenbay Aslan (Scientific Journal of Pedagogy and Economics, 2020)
Dandelion kok-saghyz (Taraxacum kok-saghyz L.Rodin) is a herbaceous plant, a source of highquality rubber. At present, Taraxacum kok-saghyz (Tks) is introduced into agriculture in Kazakhstan. "Saryzhaz" is Kazakh variety of Tks tested as a one-year culture on the experimental plots of the South-Eastern Kazakhstan (N43.1471, E77.2977). The vegetation period of Tks "Saryzhaz" from the preparation of seedlings in the greenhouse (early March) until achene development maturity in the open field takes five months. The studies of koksaghyz “Saryzhaz” as a one-year culture were repeated three times. From the 200 м2 plots, the raw root harvest was 0.35 (2017), 0.32 (2018), and 0.37 centers (2019), with a density of 10 plants per 1 м2 . The rubber content is 8 ± 3% per the dry weight of the root. By extrapolating the results of research to one hectare (at a plant density of 100,000), one can predict the harvest of a raw root from 16.0 to 18.5 centers per hectare. This article demonstrates the possibility of Tks "Saryzhaz" cultivating as a one-year culture in the South-East of Kazakhstan. Tks "Saryzhaz" passes the vegetation cycle before flowering, achene development\maturity in a short spring and early summer period of 5 months. The combination of the following conditions makes it possible to use Tks as a one-year-old culture in the South-East of Kazakhstan: the use of seedlings, sufficient moisture supply (rains, watering), increased (optimal) temperatures of the spring months for the accelerated plant development. The increase of the root crop of Tks as a one-year-old crop can be achieved through optimization of farming practices (fertilizers, stocking density) and selection work.